Differential diagnosis of orofacial pain II: associated with neurovascular, vascular and musculoskeletal disorders - Acosta-Ortiz, Rodolfo (Revista Facultad de Odontología Universidad de Antioquia, 2020)
This article is the second of three articles which describes the different pathologic conditions that should be considered in the establishment of a correct differential diagnosis in the patients presenting pain in the orofacial region. Neurovascular (migraines, cluster headaches, paroximal hemicranea), vascular (temporal ateritis, carotidinya) and musculoskeletal (tension type headache, temporomandibular disorders, myofascial pain, fibromyalgia, spinocervical disorders) disorders will be reviewed.